2014
DOI: 10.1038/nature13297
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic activity of insulin-degrading enzyme inhibitors mediated by multiple hormones

Abstract: Despite decades of speculation that inhibiting endogenous insulin degradation might treat type-2 diabetes1, 2, and the identification of IDE (insulin-degrading enzyme) as a diabetes susceptibility gene3, 4, the relationship between the activity of the zinc metalloprotein IDE and glucose homeostasis remains unclear. Although Ide−/− mice have elevated insulin levels, they exhibit impaired, rather than improved, glucose tolerance that may arise from compensatory insulin signalling dysfunction5, 6. IDE inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
255
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(285 citation statements)
references
References 27 publications
13
255
2
2
Order By: Relevance
“…This report identifies a new series of N-terminal exosite (NTE) ligands as potent IDE inhibitors and describes the effects of these molecules both in vitro and in vivo. Our results are consistent with the main findings of Maianti et al (37) but also provide additional insight into the relative importance of IDE for insulin clearance. Furthermore, we investigate the potential of IDE inhibition on enhancing insulin sensitivity in rodents.…”
Section: Several Reports Have Evaluated Idesupporting
confidence: 82%
See 1 more Smart Citation
“…This report identifies a new series of N-terminal exosite (NTE) ligands as potent IDE inhibitors and describes the effects of these molecules both in vitro and in vivo. Our results are consistent with the main findings of Maianti et al (37) but also provide additional insight into the relative importance of IDE for insulin clearance. Furthermore, we investigate the potential of IDE inhibition on enhancing insulin sensitivity in rodents.…”
Section: Several Reports Have Evaluated Idesupporting
confidence: 82%
“…Maianti et al (37) report several observations from animals treated with inhibitor 6bk. Compound treatment improved glucose clearance during OGTT experiments in lean and DIO mice.…”
Section: Several Reports Have Evaluated Idementioning
confidence: 99%
“…Support for this mechanism of insulin resistance is indicated in the fact that inhibition of IDE with BDM44768 resulted in impaired glucose tolerance [85]. However, others have reported that IDE deficiency actually improved glucose tolerance [108] and based on this, some researchers are now proposing the use of IDE inhibitors as an anti-diabetes agent [86]. Deprez-Poulain et al [85] reported that IDE is involved in pathways that modulate short-term glucose homeostasis, but casts doubt on the general usefulness in the inhibition of IDE to treat diabetes.…”
Section: Methods Of Treating Alzheimer's Disease and Type 2 Diabetesmentioning
confidence: 99%
“…Many of the diabetes studies indicate that inhibition of extracellular IDE activities may be a useful method for treating diabetes [64], [65], since extracellular IDE can interfere with normal blood glucose transport by decreasing plasma insulin levels within diabetic subjects. Although, plasma insulin levels decrease to a certain amount by increasing extracellular IDE, it is the level of cytosolic IDE synthesis, not extracellular levels, that is important for the treatment of insulin resistance in diabetic subjects.…”
Section: Clinical Impact Of Insulin Degrading Enzyme (Ide) On Alzheimmentioning
confidence: 99%
See 1 more Smart Citation